Endothelial Regulation by Exogenous Annexin A1 in Inflammatory Response and BBB Integrity Following Traumatic Brain Injury - Liu, Han; He, Junchi; Wu, Yue; Du, Yang; Jiang, Yinghua; Chen, Chengzhi; Yu, Zhanyang; Zhong, Jianjun; Wang, Zhigang; Cheng, Chongjie; Sun, Xiaochuan; Huang, Zhijian (Frontiers in Neuroscience, 2021)
Background and target Following brain trauma, Blood-brain barrier (BBB) disruption and inflammatory response are critical pathological steps contributing to secondary injury, leading to high mortality and morbidity. Both pathologies are closely associated with endothelial remodeling. In the present study, we concentrated on Annexin A1(ANXA1) as a novel regulator of endothelial function after traumatic brain injury (TBI). Methods After establishing controlled cortical impact model (CCI) in male mice, human recombinant ANXA1 (rANXA1) was administered intravenously, followed by assessments of BBB integrity, brain edema, inflammatory response and neurological deficits. Result Animals treated with rANXA1 (1μg/kg) at 1 hour after CCI exhibited optimal BBB protection including alleviated BBB disruption and brain edema, as well as endothelial junction proteins loss. The infiltrated neutrophils and inflammatory cytokines were suppressed by rANXA1, consistent with decreased adhesive and transmigrating molecules from isolated microvessels. Moreover, rANXA1 attenuated the neurological deficits induced by CCI. We further found that the Ras homolog gene family member A (RhoA) inhibition has similar effect as rANXA1 in ameliorating brain injuries after CCI, while rANXA1 suppressed CCI-induced RhoA activation. Conclusion Our findings suggest that the endothelial remodeling by exogenous rANXA1 corrects BBB disruption and inflammatory response through RhoA inhibition, hence improving functional outcomes in CCI mice.